Rapid and Facile Preparation of Giant Vesicles by the Droplet Transfer Method for Artificial Cell Construction - Shimane, Yasuhiro; Kuruma, Yutetsu (Frontiers in Bioengineering and Biotechnology, 2022)
Giant vesicles have been widely used for the bottom-up construction of artificial (or synthetic) cells and for the physicochemical analysis of lipid membranes. Although methods for giant vesicle preparation and the encapsulation of molecules within them have been established, a standardized protocol has not been shared among researchers including non-experts. Here we proposed a rapid and facile protocol for the formation of giant vesicles that enables completion within 30 min. The quality of the giant vesicles that encapsulated a cell-free protein expression system was comparable to that of the ones formed using a conventional method regarding the synthesis of both soluble and membrane proteins. We also prepared artificial cells using a lyophilized cell-free mixture and showed that an equivalent protein synthesis was achieved. Our method could become a standard method for vesicle formation suited for artificial cell research.